IDENTIFIKASI SERANGGA YANG TERJERAT DIPINGGIRAN SAWAH KISARAN PERSAWAHAN JAGUNG DAN PADI - Nofisulastri Nofisulastri (Bioscientist : Jurnal Ilmiah Biologi, 2017)
Abstract : This research is a preliminary research that the source of information obtained to be used as a reference resource of teaching materials and practicum materials on Invertebrate Systematic course especially for Biology Education students FPMIPA IIKIP Mataram. The specific objective of this study was to identify the types of insects found in rice and paddy fields using simple trapping methods using modified glue. Research stages include the selection, collection, grouping and identification of insects carried out considering the seasons (dry and rainy), pre-harvest conditions, and time (morning and afternoon). Collecting and collecting data were performed 4 times each for 2 weeks (in the dry season and the rain) at 2 points of trap sampling. The results of identification showed that the discovery of 10 families of 7 orders of insects with a total of 311 individuals. Where, the largest number of entangled in the family Coccinelidae (85 individuals), Acrylidae (71 individuals), and Reduviidae were 61 individuals.